2019
DOI: 10.1039/c9pp00247b
|View full text |Cite
|
Sign up to set email alerts
|

A quinoline-based fluorescent probe for selective detection and real-time monitoring of copper ions – a differential colorimetric approach

Abstract: A quinoline moiety was used as a building block for designing a probe for the selective detection of copper ions in a partially aqueous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Firdaus et al 58 investigated quinoline-functionalized probe 28 , which displayed the selective recognition of Cu 2+ /Cu + ions in semi-aqueous medium. The as-developed molecular sensing system provides insight into the intricate physiological and redox properties of Cu 2+ .…”
Section: Chromo-fluorogenic Probes For the Detection Of Cu2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Firdaus et al 58 investigated quinoline-functionalized probe 28 , which displayed the selective recognition of Cu 2+ /Cu + ions in semi-aqueous medium. The as-developed molecular sensing system provides insight into the intricate physiological and redox properties of Cu 2+ .…”
Section: Chromo-fluorogenic Probes For the Detection Of Cu2+mentioning
confidence: 99%
“…The underlying state-of-the-art significant photophysical mechanisms towards elucidating the chemo-mechanistic pathway of target specific analyte recognition is systematically arranged. This includes intramolecular charge transfer (ICT), 12 photoinduced electron transfer (PET), 13 fluorescence resonance energy transfer (FRET), 14 aggregationinduced emission (AIE), 15 chelation-enhanced fluorescence (CHEF), 16 CQN isomerization, 17 excited-state intramolecular proton transfer (ESIPT), 18 deprotonation, 19 H-bonding interaction, 20 nucleophilic attack 21 and metal displacement approach. 22 It is worth mentioning that the sensor materials deliberated in the present review will provide overall insight into the design and unprecedented development of organo molecular probes endowed with multifarious properties for the recognition of toxic analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other fluorescent nanomaterials such as metal organic framework (MOF), [19] noble metal nanoclusters (NCs), [20,21] organic molecules, [22] and carbon dots (CDs), [23][24][25] fluorescent polymer nanoparticles are attracting massive and broad attention due to their good biocompatibility, low toxicity and easy introduction of functional groups without introducing metals. [26][27][28] In practice, because most polymers lack fluorescent chromophore and cannot emit light by themselves, the technique of labeling fluorescent nanoparticles with fluorescent dyes is chosen.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was found that a quinoline‐based fluorescent probe was used for real‐time monitoring of copper ions and analyzes its potential on peripheral blood of humans. [ 26 ] Among the various biological important metal ions, the complexes of copper are considered to be promising alternatives over the traditionally used cisplatin drugs. [ 27,28 ] In this stare, the reaction of Cu (II) with carboxylate derivative ligands has been proven vital to dispense the better anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…These ligands make it probable to understand the persuade of different coordination sites of the carboxylate ligands from monodentate, bidentate, or chelator (symmetric or asymmetric) to bridging on the anticancer properties. [ 20–31 ] Especially in case of dinuclear copper complexes the helpfulness of the drug molecules was found to be highly effective. [ 32,33 ]…”
Section: Introductionmentioning
confidence: 99%